Clinical outcomes of online adaptive magnetic resonance-guided stereotactic body radiotherapy of adrenal metastases from a single institution - Hoegen-Saßmannshausen, Philipp; Jessen, Inga; Buchele, Carolin; Schlüter, Fabian; Rippke, Carolin; Renkamp, Claudia Katharina; Weykamp, Fabian; Regnery, Sebastian; Liermann, Jakob; Meixner, Eva; Hoeltgen, Line; Eichkorn, Tanja; et al. (Cancers, 2024)
(1) Background: Recent publications foster stereotactic body radiotherapy (SBRT) in patients with adrenal oligometastases or oligoprogression. However, local control (LC) after non-adaptive SBRT shows the potential for improvement. Online adaptive MR-guided SBRT (MRgSBRT) improves tumor coverage and organ-at-risk (OAR) sparing. Long-term results of adaptive MRgSBRT are still sparse. (2) Methods: Adaptive MRgSBRT was performed on a 0.35 T MR-Linac. LC, overall survival (OS), progression-free survival (PFS), overall response rate (ORR), and toxicity were assessed. (3) Results: 35 patients with 40 adrenal metastases were analyzed. The median gross tumor volume was 30.6 cc. The most common regimen was 10 fractions at 5 Gy. The median biologically effective dose (BED10) was 75.0 Gy. Plan adaptation was performed in 98% of all fractions. The median follow-up was 7.9 months. One local failure occurred after 16.6 months, resulting in estimated LC rates of 100% at one year and 90% at two years. ORR was 67.5%. The median OS was 22.4 months, and the median PFS was 5.1 months. No toxicity > CTCAE grade 2 occurred. (4) Conclusions: LC and ORR after adrenal adaptive MRgSBRT were excellent, even in a cohort with comparably large metastases. A BED10 of 75 Gy seems sufficient for improved LC in comparison to non-adaptive SBRT.